PENGARUH KOMPETENSI PEGAWAI TERHADAP KUALITAS PELAYANAN UPT. PERPUSTAKAAN KABUPATEN KUTAI TIMUR - Armiyati, Mimin (PREDIKSI, 2016)
This study aims to determine the level of employee competence service quality and competence of employees to service quality in UPT. Libraries East Kutai. This study uses a quantitative descriptive approach. The results showed that the variable competence positively correlated with the variable quality of service. It can be seen from the results of product moment correlation coefficient of 0.521 which empirical rs is greater than the theoretical rs at 0.374. Thus it can be said that there is a significant relationship between the variables of employee competence with the variable quality of service. The results showed also that the calculation of R-Square is 0.262, which means that varabel competence contributed 26.2% to the variable quality of service. Which means that the employees' competence variables correlated positively and significantly with the variable quality of service. Thus it can be said that the hypothesis that the writer formulated in this study can be received and verified.Â